A Critical Review of Holistic Infection Control Practices in Healthcare Systems - Alkhaldi, Hajar Salah Eid; Al Suliman, Mohammad Saeed Saleh; Al Abyah, Fayez Ahmed Hussain; Alharshan, Mahdi Salem Hamad; Salhi , Anoud Abdo Abdo; Alsaleh, Alhassan Ahmad; Al Motah, Abdulrahman Yoseif A; Al Bahary, Rashed Hussain Dhafer; Alyami, Mohammad Hadi; Alasiri, Faya Mohammed Ali (Journal of Ecohumanism, 2024)
The safety of patients and the general public has never been seriously doubted regarding infection control, especially in health facilities where nosocomial infections are still rampant. This critical review discusses comprehensive essential infection control concerns, including an evidence-based and multidimensional framework. Thus, presented in the literature and method sections, the outcomes focus on recent issues, ideas, and applications. It offers ideas about the effectiveness of adopting approaches to whole-person care to minimize the prevalence of infection and international compliance with quality healthcare. The result shows the importance of building stronger networks of effective systems against new emerging diseases.